Use of lower squares and restricted boxes In the estimation of the first-order self-regression parameter AR (1) (simulation study) - محمد, محمد جاسم (Journal of Economics and Administrative Sciences, 2009)
Use of lower squares and restricted boxes In the estimation of the first-order self-regression parameter AR (1) (simulation study)